Interdisciplinary collaborative eye examinations to protect preterm infant neurodevelopment: a quality improvement project - McCarty, Dana B.; Clary-Williams, Erika; LeBLond, Kristen D.; Liu, Tianyi; Zbornik-Thompson, Tika; Ulrich, J. Niklas; Go, Michelle S. (Frontiers in Psychology, 2024)
Infants born <31 weeks gestational age with birth weight ≤1500 grams receive routine eye examinations to screen for Retinopathy of Prematurity (ROP) while in the Neonatal Intensive Care Unit (NICU) to help prevent vision threatening complications; however, preterm infants' sensory systems are underdeveloped, and repeated exposure to painful stimuli is associated with worse developmental outcomes. Methods: An interdisciplinary NICU team designed a collaborative eye exam model (CEEM) incorporating best practice recommendations for infant pain control during exams. Pain scores and vital signs were recorded before, during, and after exams. Two sets of mixedeffects regression models with a random intercept on infants were established to investigate relationships between the intervention, birth gestational age (BGA), postmenstrual age (PMA), and outcomes associated with painful stimuli. Survey feedback was elicited from NICU stakeholders about the CEEM. Results: Thirty standard of care (SC) and 35 CEEM exams of 37 infants were included in final analysis. In infants of the same BGA, the number of desaturation events was significantly reduced in the CEEM group (p=0.003) and became 1.53 times smaller with each additional week of BGA (p=0.009). Probability of heart rate recovery within 15 minutes lowered significantly in the CEEM group (p=0.04). In SC or CEEM or between infants of the same PMA, no differences were observed for bradycardia, heart rate range, chance of heart rate recovery, or pain scores. Increases in tachycardia (p<0.001) events and desaturations p=0.006 were discovered in the CEEM group. When considering interaction effects, the CEEM appeared to reduce the number of desaturations to a greater degree for infants at earliest BGAs with attenuation of this effect with greater BGA. Regarding PMA, bradycardia and tachycardia events were reduced for infants across PMAs in the CEEM, but the effect for tachycardia improves with age, while the effect for bradycardia diminishes with age. Stakeholders agreed that the infant's eye exam experience and the staff experience was "very much" improved by the CEEM. Discussion: Despite variable findings in selected outcome measures, the CEEM was positively viewed by staff. Infants may benefit from the CEEM differently based on BGA and PMA.